Seminal Hypo- and Hypervolemia - Balagobi, B.; Raguraman, S.; Jeyendran, R.S. (Elsevier, 2018)
Semen volume is the quantity of ejaculate produced and is necessary to transport the sperm to or near the cervix during coitus. An abnormal volume may help identify why a couple has failed to conceive. The semen volume is also important to calculate the total number of sperm in the ejaculate. For clinical interpretation ejaculate volume is classified as: Aspermia and Anejaculate, no ejaculate following orgasm; Hypovolemia if the ejaculate is 0.5 mL or less; Hypervolemia if the ejaculate is more than 6.0 mL. It should be emphasized that the measurement of semen volume is an essential part of routine semen analysis since it may help identify and correct fertility impairing pathology.